Pengaruh Moderasi Beragama terhadap Keberagamaan Masyarakat Pensiun di Kelurahan Bandar Selamat Kecamatan Medan Tembung - Siregar, Yuni Sarah; Harahap, Indra; Damanik, Agusman (Lembaga Yasin AlSys, 2023)
This study aims to determine the effect of religious moderation on the diversity of the retirement community in Bandar Selamat Village, Medan Tembung District. In this study, researchers used a qualitative method that is descriptive by looking for actual and detailed data and information. The research approach used by researchers is the sociology of religion research method. The data sources of this research are primary and secondary. The data collection technique is by observation, interviews and documentation. The results of this study are; Religious moderation is a concept that emphasizes mutual respect and tolerance among different religious groups. This concept teaches that everyone has the right to choose and practice their own religion, without any pressure or intimidation from other parties. The urgency of religious moderation in religious and national life includes strengthening the essence of religious teachings in life. Based on the views of the community in Bandar Selamat Village, Medan Tembung District on religious moderation for those who have retired, it can be concluded that the majority of people are aware of the importance of religious moderation in maintaining life balance, peace of mind, and social harmony among the retired community. Some view religious moderation as an opportunity for more insight.